BEHAVIOR OF THE TRANSFER OBJECT ON THE DYNAMIC LOADS DURING THE WORKING PROCESS (Nonconventional Technologies Review, 2019)
This scientific paper presents studies and researches in the field of nonconventional technologies, namely in the field of electrical erosion processing with transfer object the metal band. The paper presents the dimensioning elements of transfer object - metallic band, as well as its resistance calculations, to the stresses on the linear part 1-2, as well as to the complex bending stresses of the metal band. It also shows the behavior of the weld seam joint (tilted) to traction and shear, as well as the computation relations corresponding to the lateral buckling load and the welded joint.
Keywords: the structural strapping elements of the metal band; the dynamic stress behavior; the resistance calculation for complex loads and the lateral buckling of the transfer object - the metal band; the behavior of the welded joint (end-to-end); traction and shearing; appropriate calculation relationships